Penerapan Manajemen Personalia dalam Upaya Meningkatkan Mutu Pendidikan di Madrasah Ibtidaiyah NW Korleko - Muh Zulkifli (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2020)
So far, the management of management at MI NW Korleko has experienced obstacles because the management is handled by personnel who are not experts in their fields. In the research field taken by the author, namely Madrasah Ibtidaiyah NW Korleko, education management is handled by personnel led by the head of the madrasah and involves several employees to manage the madrasah. This study aims to describe and analyze the implementation of personnel management that follows the procurement, appointment, placement, training and termination of personnel in an effort to improve the quality of education at MI NW Korleko along with supporting and inhibiting factors for personnel management. This research is a qualitative research, taking the background of MI NW Korleko. Data collection was carried out by observation, interviews, and documentation. Data analysis was carried out by reducing data, display data, and drawing conclusions. Data validity checks were carried out by triangulating sources and techniques and combining them with theory. The results showed: (1) The implementation of personnel management at MI NW Korleko is: (a) recruitment of personnel is carried out if there is a vacancy or because it requires additional personnel in certain fields. (b) the appointment of personnel is indicated by the issuance of a decree from the head of the madrasah in deliberation with the management. (c) assignment of personnel based on the expertise possessed by personnel, which begins through internal selection by senior personnel. (d) training for MI NW Korleko personnel consists of two coaching through regular meetings which are held every month and coaching carried out conditionally based on needs. (e) dismissal at MI NW Korleko is carried out automatically if the manager is no longer part of the madrasah or has passed away. (2) Efforts to improve the quality of education are: (a) personnel development. (b) a clear division of personnel duties in the description. (c) communication between administrators. (d) holding a santri forum. (e) arranging a learning syllabus for the MI NW Korleko